Clear cell odontogenic carcinoma of maxilla: A rare case in a rarer presentation. Issue 1 (January 2016) - Narula, Vineet; Sharma, Divya; Bhargava, Eishaan Kamta; Meher, Ravi; Mandal, Shramana; Rana, Kanika
Abstract: Clear cell odontogenic carcinoma (CCOC) is a rare odontogenic tumor occurring predominantly in the mandible, most commonly in the 5th to 7th decades. We describe a case of CCOC of maxilla, in a 28-year-old female presenting with right-sided facial swelling and nasal obstruction. The patient underwent a right-sided extended total maxillectomy with orbital exenteration with local forehead rotation flap repair followed by postoperative radiotherapy. Histological and immunohistochemical features were consistent with CCOC. This case exemplifies the need for reviewing ultrastructural details and immunohistochemistry in a clear cell tumor of the jaw.